Strategi Jitu Mengatasi Kredit Macet pada Badan Usaha Lembang Sa’dan Andulan - Mince Batara; Marchelin Marchelin; Agustinus Mantong; Stefani Marina Palimbong; Helba Rundupadang; Olivia Devi Yulian Pompeng (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Lembang Sa’dan Andulan has great potential for local economic development through the weaving industry but faces challenges in raw material supply and bad credit that hinder business sustainability. This research aims to provide assistance in identifying the root causes of bad credit, formulating effective credit management strategies, and enhancing the capacity of the management of Badan Usaha Lembang Sa’dan Andulan. The methods used include financial management training, developing a credit assessment system, improving communication, and business mentoring. The results show that the management now understands the impact of bad credit and can analyze its causes. They are beginning to implement the 5C and 7P methods in assessments and business development, and show active roles in financial management. It is hoped that this activity will encourage economic growth in the Lembang Sa’dan Andulan community and create significant social change.